A universally dispersible graphene-based ink modifier facilitates 3D printing of multi-functional tissue-engineered scaffolds. (April 2022) - Hu, Chengshen; Chen, Zhigang; Tang, Lan; Liu, Juan; Yang, Jirong; Lai, Wing-Fu; Wu, Tong; Liao, Siyuan; Zhang, Xintao; Pan, Haobo; Ruan, Changshun
Graphical abstract: Highlights: A universally dispersible graphene oxide-based polyurethane (GO-PU) is successfully prepared. This GO-PU can be used as an ink modifier to endow the arbitrary bioink matrixes with better mechanical properties and multifunction. In vitro and in vivo toxicity test showed that GO-PU has excellent biocompatibility. Abstract: 3D-printed bioscaffolds for the realization of individualized tissue regeneration remains challenging due to the limitation in terms of current biomaterial inks. Exploring a universal ink modifier to enhance the properties of the arbitrary inks for 3D printing of multi-functional scaffolds is therefore an alternative. Herein, a universally dispersible graphene oxide-based polyurethane (GO-PU) ink modifier with network structure constituting amphiphilic polyethylene glycol (PEG) and nanoscale GO (nGO) is presented for the first time. GO-PU can be stably dispersed in various organic and aqueous solutions for 24 h without obvious aggregation, far superior to pure nGO. The excellent printability of GO-PU is demonstrated to fabricate pure GO-PU and GO-PU modified composite scaffolds in which GO-PU is used as ink modifiers. The addition of GO-PU with 5% (ww%/wt%) contents into PLGA or PEGDA can not only improve their mechanical properties without decrease printability, but also endow the additional performances with the resulting scaffolds from the incorporated functional nGO segments, like photo-triggered release ability. In addition, the results of in vitro and in vivo toxicity tests confirmed that GO-PU is biocompatible, indicating that this facile and universal approach for introducing graphene materials into 3D-printed scaffolds is with a great potential for tissue regeneration.